Evaluation of irreversibility in an ammonia-water absorption refrigeration system using three different mathematical models to calculate the thermodynamic properties - Vera Romero, Iván; Heard Wade, Christopher Lionel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 9-19).